Determination of Fish Species Diversity of Tagwai Lake, Minna, Niger State, Nigeria - Aliyu E. J.; Nmadu E. Y.; Atile J. I. (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study investigates the fish species diversity of Tagwai Lake, Minna, Niger State, Nigeria, over a four-month period from August to November 2020. A total of seven fish species were identified during the study. Clupeid sierrathrissa was the most abundant, accounting for 4,780 individuals (43.30%), followed by Allestes macrolepidotus with 2,500 individuals (22.65%), and Oreochromis niloticus with 2,494 individuals (22.60%). Other species included Synodontis courteti (935; 8.47%), Clarias gariepinus (316; 2.86%), Mormyrus hasselquisti (13; 0.12%), and Labeo senegalensis (1; 0.01%). Analysis of sex ratios revealed a predominance of females in Tilapia, Allestes macrolepidotus, Clarias gariepinus, Clupeid sierrathrissa, and Mormyrus hasselquisti (ratios of 1:3, 1:7.3, 1:11.1, 1:5.6, and 1:2 respectively). Labeo senegalensis showed no female representation (1:0), while Synodontis courteti exhibited a slightly male-biased ratio (1.3:1). The study found that fish species diversity in Tagwai Lake is influenced by intensive fishing activities involving a variety of gear types, including different mesh sizes, traps, and hook-and-line methods. These findings highlight the need for sustainable fishing practices to preserve biodiversity in the lake ecosystem.